The Venn-MacColl Dispute in Nature. Issue 3 (2nd July 2020) - Verburgt, Lukas M.
Abstract : During 1881, the British logicians John Venn and Hugh MacColl engaged in a brief dispute in Nature about 'symbolical logic'. The letters to the editor shed interesting light on the early reception of MacColl's contributions to logic and his position in the logical community of the Victorian era. Drawing on the correspondence between Venn and William Stanley Jevons, this paper analyzes the background and context of these letters, adding to the recent interest in the social dimensions of the development of British algebraic logic in the confusing intermediary period between the 1870s and 1890s.